PENERAPAN LOAD CELL PADA MESIN PENGORENG KERUPUK OTOMATIS BERBASIS ARDUINO UNO & PLC - Damayanti, Eva; Saptaji, Aji (Jurnal TEDC; Vol 18 No 1 (2024): JURNAL TEDC, 2024)
The purpose of this research is to make an automatic cracker measuring device using Arduino Uno as its control center which contains a program made in the Arduino IDE software. This tool is required to run a conveyor where if a cracker has been measured or weighed according to the 20gram setpoint specified in the program, a conveyor will run automatically. Here the weight sensor uses Load cell as a weight sensor and output in the form of a relay module, DC motor, LCD, to monitor and run a conveyor. Based on the measurement results table, the percentage error rate is input data 20 grams has a percentage error rate of 10.84%, input data 21 grams has a percentage error rate of 7.228%, input data 22 grams has a percentage error rate of 6.209%, input data 23 grams has a percentage error rate of 8.660%, input data 24 grams has a percentage error rate of 6.908%, and input data 25 grams has a percentage error rate of 7.44%. The analysis results have a percentage error rate of 8.660%, 24gram input data has a percentage error rate of 6.908%, and 25gram input data has a percentage error rate of 7.44%. So it can be concluded that the percentage of error rate can be caused by human error during measurement so that the accuracy of the load cell sensor measurement. It is concluded from the table above that when the weight of the cracker raw material given in the weighing process carried out by the load cell is below 23 grams, the process of frying crackers in the sieve will be less than the capacity. This is related to the process of developing fried crackers. When the crackers that are cooked by expanding in the sieve are less than the capacity, it will be said to be good because the crackers will not fall or exceed the capacity. So that the machine can accommodate the frying process of cracker material of no more than 23 grams because it adjusts to the shape of the pan with a diameter of 30 cm and the sieve used.